The Impact of Bullying on Adolescent : A Systematic Review - Paramita, Sintia; Palipung, Rizky Yuniarti; Ni'matuzahroh, (International Journal of Scientific Research and Management (IJSRM), 2024)
Bullying is an act that can hurt others both verbally and non-verbally which is carried out continuously and over a long period of time. Bullying behavior can cause the victim to be in a constant state of intimidation. The purpose of this systematic review is to determine the impacts of bullying behavior on adolescents. There are twelve journals that provide information related to the dangers and what are the impacts of bullying behavior on adolescents. The literature search was conducted using one database, Scopus. Only studies that were published in English and examined bullying and the impact of bullying were included in this systematic review. The results of this systematic review revealed that bullying behavior has many negative impacts on both perpetrators and victims, including disrupting mental health and physical health, lowering academic achievement, and can even lead to suicidal behavior.